RANCANGAN APLIKASI KALKULATOR ILMU FALAK BERBASIS SMARTPHONE - Abdul Hayat; Esa Rizki Hari Utama (Universitas Raharja, 2018)
In practice, astronomy studies about how to calculate the direction of qibla, the beginning of prayer time, the beginning of the month of Hijri and the possibility of eclipses. Usually people who are studying astronomy do calculations by manual. Performing calculations manually has a risk in terms of calculation accuracy. Therefore, the presence of this application of astronomy calculators is expected to benefit people, especially Moslems who want to know the position of the Qibla for prayer, to estimate the beginning of the Hijri month, the Hijri calendar, and so forth. This article is an idea how to design a mobile smart phone-based astronomy calculator application. The method begins with literature studies from books and articles on astronomy that have been developed by some previous researchers; then the design is used to describe how the application model of the calculator of astronomy according to smart phone format as a mobile application, either Android or iOS. It is expected that with this mobile application can spread as widely as possible for the utilization of astronomy to all people who need, especially when doing the activities of reckoning and sighting of moon